2012
DOI: 10.1002/jmr.2216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the selectivity of a ligand complex with CDK2/CDK1: a molecular dynamics simulation approach

Abstract: Cyclin-dependent kinases (CDKs) are core components of the cell cycle machinery that govern the transition between phases during cell cycle progression. Abnormalities in CDKs activity and regulation are common features of cancer, making CDK family members attractive targets for the development of anticancer drugs. Their inhibitors have entered in clinical trials to treat cancer. Very recently, Heathcote et al. (J. Med. Chem. 2010, 53:8508-8522) have found a ligand BS194 that has a high affinity with CDK2 (IC(5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 81 publications
(85 reference statements)
1
27
0
Order By: Relevance
“…The binding site residues of HER2, EGFR and CXCR2 produced hydrophobic, hydrophilic maps and hydrogen binding possibilities which may guide the protein-ligand docking analysis (Tripathi et al, 2012). In order to rationalize the described structure characterization, protein preparation and site map prediction results, molecular docking studies were undertaken on epifriedelanol (isolated compound) and carboplatin (FDA approved drug for ovarian cancer) complexes with X-Ray crystal structure of HER2, EGFR and CXCR2 (ovarian cancer targets).…”
Section: Discussionmentioning
confidence: 99%
“…The binding site residues of HER2, EGFR and CXCR2 produced hydrophobic, hydrophilic maps and hydrogen binding possibilities which may guide the protein-ligand docking analysis (Tripathi et al, 2012). In order to rationalize the described structure characterization, protein preparation and site map prediction results, molecular docking studies were undertaken on epifriedelanol (isolated compound) and carboplatin (FDA approved drug for ovarian cancer) complexes with X-Ray crystal structure of HER2, EGFR and CXCR2 (ovarian cancer targets).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of homology modeling methodology, it provides us an alternative way to study from the structure-based point of view. Structures are built based on templates by homology modeling for proteins without dissolved crystal structure (Gallina et al, 2014;Thomas et al, 2014;Tripathi et al, 2012). Besides, homology modeling method provides the opportunities for identifying potential agonists or antagonist by structure-based virtual screening (Pala et al, 2013;Tarcsay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…found that Leu83 is a key residue that recognizes BS194 more effectively with CDK2 with good binding free energies rather than CDK1. Energetic analysis reveals that van der Waals interaction and nonpolar contributions to solvent are favorable in formation of complexes and amine group of the ligand, which plays a crucial role for binding selectivity between CDK2 and CDK1 . Aixiao et al .…”
Section: Resultsmentioning
confidence: 99%